Children May Experience Long Term Effects of Disaster - Powell, Joyce (My University, 1993)
This publication explains that children may experience emotional and behavioral effects for months, one year or even two years following a disaster.
MF1146_1993_09
Keywords: MF1146; Home and Family; Health and Safety; MF